RE-EVALUATION THE FREQUENCY OF CUTANEOUS MANIFESTATIONS IN PATIENTS ON HEMODIALYSIS (Iraqi Journal of Medical Sciences, 2016)
Background: Hemodialysis patients experience frequent and various cutaneous manifestations. Chronic renal failure (CRF) is a clinical state, which results in declining of kidney functions.Objective:To evaluate the frequency and nature of cutaneous lesions associated with CRF patients on hemodialysis.Methods: Fifty patients with chronic renal failure on hemodialysis in Al-Kadhimiya Teaching Hospital, Dialysis Center from the period of February 2012- May 2012 were conducted in this case series study.Results:All patients included in this study had at least one cutaneous manifestation related to chronic renal failure. The most frequent findings were pruritus (100%), pallor (100%), xerosis (100%), hyperpigmentation (74%), petechae (40%), ecchymosis (30%) and wrinkles (30%). Nail changes were half and half nail (76%), koilonychias (48%) and splinter hemorrhage (28%). Oral changes were xerostomia (88%) and ulceration (52%). Other manifestation like hair changes (42%) was seen.Conclusion:Chronic renal failure is associated with various cutaneous manifestations caused by hemodialysis or the disease itself. The most frequent findings; pruritus, pallor and xerosis. The early diagnosis of cutaneous changes may decrease the morbidity and eventually lead to the improvement of life quality in these patients.Keywords:Chronic renal failure, hemodialysis, cutaneous manifestations.
Keywords: Chronic renal failure; hemodialysis; cutaneous manifestations